Government Policy on Waste Management in Panca Rijang District, Sidenreng Rappang Regency - Andi Artika Sari; Barisan; Irwan (Global Writing Academica Researching and Publishing, 2026)
This study aims to analyze public policy regarding waste management in Panca Rijang District, Sidenreng Rappang Regency; identify factors influencing its implementation; and formulate an effective and sustainable waste management policy model. The study employs a qualitative method with a descriptive approach. Data were collected through in-depth interviews, observation, and documentation. Research informants included the Panca Rijang District Head, the Sidenreng Rappang Regency Environmental Agency, sub-district heads, sanitation workers, and local residents. Data analysis utilized the Miles and Huberman interactive model, comprising data reduction, data display, and conclusion drawing, and was reinforced by analysis using NVivo 12 Plus software. The results indicate that the implementation of waste management policy in Panca Rijang District has not yet proceeded optimally. Key issues identified include low rates of household waste sorting, limited waste collection fleets, suboptimal utilization of 3R (Reduce, Reuse, Recycle) waste facilities, and low community participation. Policy effectiveness is influenced by policy and regulatory factors, implementation factors (facilities, infrastructure, human resources, and budget), and community behavior. Regarding the policy network, the government remains the dominant actor, while the involvement of the public, community groups, and the private sector remains suboptimal. This study recommends a Multi-Stakeholder Collaboration-Based Waste Management Policy Model, achieved through strengthened inter-actor coordination, improved facilities and infrastructure, optimized 3R facilities, and enhanced public education and participation to realize effective and sustainable waste management tailored to the local characteristics of Panca Rijang District.